2023
DOI: 10.5114/reum/160209
|View full text |Cite
|
Sign up to set email alerts
|

Update on the neuromonitoring procedures applied during surgeries of the spine – observational study

Abstract: IntroductionMotor evoked potentials (MEPs) are currently considered as a more useful method for neurophysi-ological intraoperative monitoring than somatosensory evoked potentials in cases of surgery applied to patients with adolescent idiopathic scoliosis. The non-invasive approach is preferred to modify MEP recordings, criticizing, in many cases, the fundamentalism for neurophysiological monitoring based only on needle recordings. The aim of the review is to provide our own experience and prac-tical guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 14 publications
5
11
0
Order By: Relevance
“…Similarly to Gadella et al [30] and Duffler et al [31], we observed in T0 twice as many incidents of impedances of surface electrodes than needle electrodes, which did not significantly influence the signal-to-noise ratio parameter, and demonstrated the high utility of both methods in neuromonitoring procedures. Our previous pilot results on improving the neuromonitoring methodology [32] are fully compatible with their observations. Moreover, taking into account the fact that IS surgeries are pediatric and the consequences of neuromonitoring procedures using TES when MEPs are recorded with needle electrodes can be ecchymosis and bruises associated with the stimulation-related muscle movements, local nerve damage or infections in rare cases [50], and, frequently, postoperative skin reddening [51], recording from the muscle's surface is more beneficial.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similarly to Gadella et al [30] and Duffler et al [31], we observed in T0 twice as many incidents of impedances of surface electrodes than needle electrodes, which did not significantly influence the signal-to-noise ratio parameter, and demonstrated the high utility of both methods in neuromonitoring procedures. Our previous pilot results on improving the neuromonitoring methodology [32] are fully compatible with their observations. Moreover, taking into account the fact that IS surgeries are pediatric and the consequences of neuromonitoring procedures using TES when MEPs are recorded with needle electrodes can be ecchymosis and bruises associated with the stimulation-related muscle movements, local nerve damage or infections in rare cases [50], and, frequently, postoperative skin reddening [51], recording from the muscle's surface is more beneficial.…”
Section: Discussionsupporting
confidence: 85%
“…In this paper, we describe the results of the studies with the methodology of the MEP recordings using the surface electrodes from the tibialis anterior muscle bilaterally, which is more and more widely used not only in pre-and postoperative diagnostic purposes but also has been proven to be precise enough for intraoperative monitoring in comparison to the standard needle electrodes [30,31]. Our previous pilot results on improving the neuromonitoring methodology [32] are fully compatible with such observations. It has not yet been documented whether the results of MEP recordings induced by the transcranial single magnetic stimulus can be compared with MEPs induced with the trains of electrical stimuli applied intraoperatively for diagnostic evaluation of the spinal neural transmission.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Neurophysiological assessment has the most important intraoperative significance when neuromonitoring the conduction of neural impulses within the spinal cord pathways [25]; however, preoperatively, in patients with IS, it supports the clinical assessments when making decisions about surgical treatment [26]. Few studies in the field of clinical neurophysiology presenting postoperative recordings, especially of motor-evoked potentials, proved an immediate functional improvement in the efferent conduction of spinal pathways in IS patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…The standards of neuromonitoring are constant and consist of checking every step of the surgical procedure and reacting to improper incidents [ 20 ]. Although a consensus-based checklist to guide the surgeon’s reactions to IONM changes and best-practice guidelines for their recording have been formulated [ 21 ], and their agreement has been confirmed and validated [ 22 ], new concepts have since been developed [ 23 , 24 , 25 ]. It is obvious that the surgical team of spine surgeons, anesthesiologists, and neurophysiologists cooperate more efficiently if their experience, technical skills, and equipment are advanced [ 26 ].…”
Section: Introductionmentioning
confidence: 99%